Role of the orientational subsystem in the expansion of pure CF6, CHCl3, C6H6, CCl4 and N2O with Kr impurity: Low-Temperature Thermodynamics and Structure - Zholonko, N.N.; Tsibulin, V.V.; Sarwar, I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The linear expansion coefficients of solid bulk samples of N2O with Kr 5% impurity are measured by an absolute dilatometric method in comparison with pure N2O in the temperature range 80–150 K. An additional unusual orientational effect is discussed. An analysis of the data frommeasurements of the linear expansion coefficients of pure solid SF6, CHCl3,C6H6, CCl4 in comparison with solid Xe in the temperature range 80–170 K is carried out in order to determine the role of molecules` orientational disordering in the thermal expansion of the given condensed systems. The results are discussed in connection with the problem of determining the contribution of orientational subsystems with different types of molecular symmetry to the total thermal expansion and its behavior in various temperature intervals of solid phase existence.